PENGGUNAAN BAHAN HUMAT DAN KOMPOS UNTUK MENINGKATKAN KUALITAS TANAH BEKAS TAMBANG NIKEL SEBAGAI MEDIA PERTUMBUHAN SENGON (Paraserianthes falcataria). - Ikbal Ikbal; Iskandar Iskandar; Sri Wilarso Budi R (Graduate School Bogor Agricultural University (SPs IPB), 2016)
The purpose of this study was to analyze the effect of humic materials and compost on soil chemical properties and plant growth. The research was conducted in the Nickel Mine Land in PT Aneka Tambang (Persero) Tbk., Pomalaa, Southeast Sulawesi. Soil analysis was carried out in the Laboratory of Soil Research Institution, Bogor. Experiments were performed using randomized block design factorial 2 factors, with: Humic material level (0; 0.5; and 1.0 ml/plant) and compost level dosage (0.0; 1.0; and 2.5 kg/plant). The results showed that humic material and compost affect the improvement of the soil chemical properties. The combination of humic material and compost were able to increase N total, CEC, P, available base and saturation exchangeable. Humic material able to reduce Cr and Ni available in the soil. Whereas compost and combination of humic materials and compost able to reduce Ni available in the soil. Humic material and compost were also significantly affect the plant height, root lenght, diameter, nodule, and biomass. The best treatment was 1.0 ml and compost 2.5 kg to plant growth.